2023
DOI: 10.3390/app13127205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Excavation Ergonomics of Drill and Blast Method Based on Game Theory G2-EW-TOPSIS Model

Abstract: The demand for tunnel construction continues to grow by leaps and bounds. Therefore, tunnel mechanization construction is receiving more and more attention for improving excavation ergonomics. To enhance the scientific and comprehensive evaluation results of tunnel drilling and blasting method excavation ergonomics, a set of evaluation methods of tunnel drilling and blasting method excavation ergonomics based on the game theory G2-EW-TOPSIS model is proposed. From the three dimensions of drilling efficiency, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In terms of construction organization safety factors, Einstein et al proposed tunnel decision support (DAT) to predict various uncertain risk factors in the process of underground construction organization and found that the tunnel construction process can be continuously updated through exploration [24]. Based on the game theory G2-EW-TOPSIS model, Yang et al found that construction quality is the core index in the process of tunnel construction [25]. Guha used factor analysis, multiple regression, and other methods to analyze the safety management problems of existing construction organizations in Kolkata, India.…”
Section: Construction Organization Of Urban Rail Transit Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of construction organization safety factors, Einstein et al proposed tunnel decision support (DAT) to predict various uncertain risk factors in the process of underground construction organization and found that the tunnel construction process can be continuously updated through exploration [24]. Based on the game theory G2-EW-TOPSIS model, Yang et al found that construction quality is the core index in the process of tunnel construction [25]. Guha used factor analysis, multiple regression, and other methods to analyze the safety management problems of existing construction organizations in Kolkata, India.…”
Section: Construction Organization Of Urban Rail Transit Projectmentioning
confidence: 99%
“…According to the principle of maximum membership degree, the evaluation grade of the construction organization resilience of Nanchang West Station in the first section of the first phase of Nanchang Metro Line 2 is determined to be grade IV (higher resilience) using Formula (25). According to Formula (26), it is finally found that the comprehensive score value j * of the construction organization resilience of Nanchang West Station is 4.0305.…”
Section: Determine Evaluation Gradementioning
confidence: 99%
See 1 more Smart Citation